DFID's new urban discourse: a critique. Issue 5 (1st September 2020) - McGill, Ronald
Abstract : DFID is a self-confessed late entrant to the urban discourse. Two major recent proposals give this assertion credence. First is the collective Cities and Infrastructure for Growth (CIG) programme, to strengthen the management of urban and energy sectors and boost investment in infrastructure. Second is the African Cities Research Programme, to produce new knowledge and evidence on African cities as systems. In turn, from both practical and research standpoints, they seek to reduce poverty and enhance national prosperity through the known advantages of urbanisation, while impacting on its negative dimensions. This critique seeks to test the assumptions underscoring both proposals.